Comparing apples and oranges - model-based assessment of different tsetse-transmitted trypanosomosis control strategies - McDermott, John J.; Coleman, P.G. (Elsevier, 2001)
The current control strategies for tsetse-transmitted trypanosomosis in cattle (trypanocidal drugs tsetse control and trypanotolerant cattle) are briefly reviewed and their adoption rates in different geographic regions of sub-Saharan Africa are presented. The impact of these control strategies and the potential use of vaccines should they be developed, on trypanosomosis transmission were compared using a mathematical model. The relative trypanosomosis prevalence compared with no control was estimated across a range of control coverages (from none to complete control coverage) by varying the change in specific model parameters influenced by individual control measures. Based on this comparison, the relative rankings of the effect of control strategies on reducing disease prevalence were: vector control, vaccination, and drug use, in that order. In this model, trypanotolerance was assumed to decrease disease prevalence, but not to influence transmission. Differences in the predicted impact of control measures on the transmission of human sleeping sickness are discussed. Finally, the role of transmission model outputs as inputs for economic models to guide investment decisions for trypanosomosis control is emphasised.